GIS-Based Biomass Energy Sustainability Analysis Using Analytical Hierarchy Process: A Case Study in Medellin, Cebu - Galang, Wenyville Nabor; TabaÃ±ag, Ian Dominic; Loretero, Michael (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The increasing demand for energy accounts for an alternative energy source. The search for biomass being abundant in an agricultural country is a suitable option to power a community. This paper used Analytical Hierarchy Process (AHP), which includes the organized hierarchy of various selection criteria, the assessment of the relative value of criteria, the comparison and an aggregate rating of the alternatives for each criterion. Specifically, the methodology used was the combination of multi-criteria and weighted-overlay analysis in a Geographical Information System (GIS) environment to provide a spatial overview of the sustainable location for sugarcane residues production in Medellin, Cebu. The study was able to identify Caputatan Sur and Canhabagat as sustainable locations for sugarcane residue production with respect to topography, cultivation area and accessibility. These locations represent 26% of the total cultivation area and average sugarcane production of the locality. The result of this study is an initial step in the support for the utilization of sugarcane residues to answer energy demand in remote areas and further promote the use of indigenous resources for energy generation.